The future of higher education in Ireland: a postcolonial perspective. Issue 5 (3rd September 2018) - Burke, Christina
ABSTRACT: The transformation that Irish higher education (HE) has undergone since the mid-2000s has been particularly rapid and unidirectional. Following the Global Financial Crisis, the Irish Government sought to take control of tertiary education in an attempt to shield the country from future economic shocks. This paper succinctly discusses the circumstances leading to the current policy position and what these changes have meant for Irish HE. A postulation that neoliberalism will inevitably deepen further within Irish HE will be explored through the lens of Postcolonial theory. In conclusion, I will show that the application of this theoretical stance may succeed in buffering many of the effects of neoliberalism to ensure ample space in HE for all subject areas and disciplines.